Impact of cardiovascular health status on the dose-response relationship between physical activity and incident morbidity and mortality. (25th November 2020) - Bakker, E.A; Oymans, E.J; Hopman, M.T.E; Thijssen, D.H.J; Eijsvogels, T.M.H
Abstract: Background: Although the health benefits of a physically active lifestyle are well-known, there is ongoing discussion about the dose-response relationship between physical activity (PA) and incident morbidity/mortality, and whether this association may be affected by cardiovascular health status. Purpose: We compared the dose-response relationship of PA, incident major cardiovascular events (MACE) and all-cause mortality between healthy individuals and individuals with cardiovascular disease risk factors (CVRF) or cardiovascular diseases (CVD). Methods: This study used data from Lifelines, which is a multi-disciplinary population-based cohort including 167, 729 participants from the northern population of the Netherlands. Adults (>18 yrs old) without severe illnesses or limited life expectancy (<5 yrs) were included (N=143, 059). PA volumes were presented as Metabolic Equivalent of Task (MET) minutes/week, and divided into quartiles (Q1-Q4). The primary outcome was a composite endpoint of incident MACE (i.e. myocardial infarction, stroke, heart failure, CABG or PCI) and all-cause mortality. Results: Age (42±12 yrs) and proportion of male (40%) was lower in healthy individuals compared to individuals with CVRF (54±11 yrs, 45% male) or with CVD (57±13 yrs, 62% male). During a median follow-up of 7 years (IQR 6–9), 2, 485 events occurred in healthy individuals (2% of n=112, 018), 2, 214 in individuals with CVRF (8% of n=27, 982) and 1, 100 (36% of n=3, 059) in those with CVD. Higher PA volumes were associated with a lower risk of adverse outcomes in healthy individuals and in individuals with CVRF (Table 1). In contrast, only the highest PA quartile was associated with a risk reduction for adverse outcomes in individuals with CVD (Table 1). Also, effect-modification was present in the dose-response relationship between PA volumes and health outcomes for CVD (P-interaction<0.05), but not for healthy or CVRF. Conclusions: Cardiovascular health status impacts the dose-response relationship between PA volumes and adverse outcomes. These findings indicate that PA recommendations should be adjusted to an individual's health status for achieving maximal health benefits from a physically active lifestyle. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The work of T.M.H.E is supported by the Netherlands Heart Foundation. The Lifelines Biobank initiative received a subsidy from the Dutch Ministry of Health, Welfare and Sport, the Dutch Ministry of Economic Affairs, the University Medical Center Groningen [UMCG], University Groningen and the Northern Provinces of the Netherlands.